Relationship between skeletal bone mineral density and subjective masticatory difficulty - Seok Woo Hong; Jeong-Hyun Kang (BMC, 2022)
Abstract Background Masticatory ability is an essential factor for sustaining quality of life and social and systemic well-being, particularly in elderly. This study aimed to reveal the association between subjective masticatory difficulty and skeletal bone mineral density (BMD). Methods Data from the Korean National Health and Nutrition Examination Survey, which was conducted from 2008 to 2011 were analyzed. This study included 13,092 Koreans (5656 males, 7436 females) over 50 years of age. Masticatory difficulty was evaluated based on a self-reported questionnaire. Areal BMD of the total hip, femoral neck, and lumbar spine as well as lean body mass were determined using dual-energy X-ray absorptiometry. Data about the sociodemographic characteristics, physical activity, number of teeth present, sum of decayed, missing, and filled permanent teeth (DMFT) index and Community Periodontal Index (CPI) were collected. Multivariate logistic regression analysis was conducted to analyze associations between subjective masticatory difficulty and BMD, adjusting for the confounding covariates. Results Significant differences were observed in the areal BMD of the total hip, femoral neck, and lumbar spine as well as lean body mass accordance with the presence of subjective masticatory difficulty in both males and females. The number of teeth, DMFT, and CPI score did not show significant differences based on the presence of self-reported satisfaction of chewing performance in both males and females. Results from multivariate logistic regression demonstrated that the subjective masticatory difficulty showed significant interactions with skeletal BMD and the associations between masticatory satisfaction and BMD of the total hip and femoral neck were more prominent in females compared to those in males. Conclusions The skeletal BMD, particularly areal BMD of the femoral neck was significantly associated with subjective masticatory difficulty in elderly, especially in elder females.